Mobilization of navicular and its effects on balance and stability limits in young healthy subjects - Couto, A.; Cardoso, M.; Lopes, S.; Carvalho, R. (Annals of physical and rehabilitation medicine, 2018)
The foot is an important component of the musculoskeletal system, responsible for the interaction between the base of support and the lower limb segments, allowing an adequate distribution of weight bearing in the foot. Motor tasks, such as, standing and/or gait, depends on the postural control system, which is related to the projection of the center of mass on the ground and the limits of stability. Verify the effect of navicular mobilization on the balance and the stability limits. Experimental study was performed. Forty university students, were randomly assigned to two groups: control group (mean age 22±2.4 years) and experimental group (mean age 22±2.7 years). The Pachymeter was used to assess navicular height. Balance and stability limits were assessed by Single Leg Stance, Functional Reach Test, and Y-Balance Test, at two sequential time periods. Subjects from experimental group underwent an intervention focused in navicular mobility for 10min. The t-Student and Mann-Whitney test was performed to compare differences between groups, while the Wilcoxon and t-Student test was used to compare moments. The level of significance was α=0.05. After intervention, the experimental group had differences in navicular height, Functional Reach Test (P<0.001), Single Leg Stance (P=0.004) and in Y-Balance Test (P<0.001). Moreover, the experimental group showed an increase in Functional Reach Test (P=0.003) and Y-Balance Test (P<0.001) compared to control group, after intervention. This study showed that the navicular mobilization increases the balance and the stability limits in healthy young subjects.